Evaluating rare earth elements as a proxy for oil–source correlation. A case study from Aer Sag, Erlian Basin, northern China. (October 2015) - Gao, Ping; Liu, Guangdi; Jia, Chengzao; Ding, Xiujian; Chen, Zhelong; Dong, Yiming; Zhao, Xuan; Jiao, Weiwei
Highlights: An attempt was made using rare earth elements (REE) for oil–source correlation. REE cannot be used alone for oil–oil and/or oil–source correlations. Factors controlling REE distributions in crude oils were preliminarily established. Abstract: The use of rare earth elements (REE) for oil–source correlation has not yet been established. In order to evaluate the potential of REE as proxies for oil–source correlation, we used traditional correlation approaches, including biomarkers and trace elemental ratios (V/Ni and Ni/Co), to identify the source rock of oil sands using isolated organic extracts of mudstones and oil sands, and by analyzing the organic extracts and their corresponding whole rock material for REE compositions by inductively coupled plasma-mass spectrometry (ICP-MS). Oil–source correlations using REE were not consistent with conclusions based on biomarker data and trace element ratios. Only one pair of oil–source rock relationship was successfully established using REE. REE concentrations of crude oils could possibly be controlled by the quantities of metal complexes and functional groups that provide complexing sites for V and REE as well as secondary alteration processes (e.g., thermal alteration and biodegradation). REE patterns might be linked to the organic matter types of source rocks. Although an accurate oil–source relationship failed to be established using REE in this study, REE could potentially be a novel complementary proxy for oil–oil and/or oil–source correlations when supplemented by traditional correlation approaches, including biomarkers.